Does the crowd matter in refereeing decisions? Evidence from Spanish soccer - Picazo-Tadeo, A. J.; Gonzalez-Gomez. F.; Guardiola, J. (International Journal of Sport and Exercise Psychology, 2017)
This paper analyses referee home bias with data from the First Division of the Spanish Football League between the 2002/03 and 2009/10 seasons. The aim is to assess the behaviour of the referee in relation to two decisions, namely free kicks awarded and players booked. The main contribution of this paper is the way in which it analyses referee bias; free kicks and bookings are not considered independent elements, instead it is presumed that the number of free kicks awarded has an impact on the cards shown. Regarding methodology, two random effects panel-data regression models are estimated. The results obtained do not confirm, at least in the period under analysis, that Spanish soccer referees have been biased in favour of the home team when it comes to awarding free kicks. However, once a free kick has been awarded, there does appear to be a referee home bias in the disciplinary sanctions taken against a player for committing a foul. These findings suggest that when there is a large crowd in the stadium, the referee tends to be more inclined to book away team players than home players. A reasonable hypothesis that could explain this result is that the amount of time the referee has to make a decision affects the final outcome. While referees are not biased when it comes to awarding a free kick, they are when given more time to make a decision, as there are more opportunities for social pressure to work in favour of the home team.